2022
DOI: 10.1186/s12014-022-09351-3
|View full text |Cite
|
Sign up to set email alerts
|

Airway fibrin formation cascade in allergic asthma exacerbation: implications for inflammation and remodeling

Abstract: Background Airway remodeling in patients with asthma, which leads to a decline in pulmonary function, is likely the result of repeated exacerbations often provoked by aeroallergen exposures. Aeroallegen exposure triggers a stereotypic response orchestrated by growth factor cytokines and other protein mediators. This results in a late-phase allergic reaction characterized by vascular permeability, recruitment of activated leukocytes, and activation of structural cells of the airway. The spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…[31,32] Fibronectin-1 (FN1) signi cantly affects asthma by aiding airway remodeling and enhancing in ammatory cell activity and brosis. [33] After allergen exposure, the production of FN1, particularly its extra domain A (ED-A) variant, is associated with signi cant structural alterations in the airways, leading to reduced lung function. [34] This relationship highlights FN1 as a possible target for asthma treatments aiming to enhance lung function metrics.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] Fibronectin-1 (FN1) signi cantly affects asthma by aiding airway remodeling and enhancing in ammatory cell activity and brosis. [33] After allergen exposure, the production of FN1, particularly its extra domain A (ED-A) variant, is associated with signi cant structural alterations in the airways, leading to reduced lung function. [34] This relationship highlights FN1 as a possible target for asthma treatments aiming to enhance lung function metrics.…”
Section: Discussionmentioning
confidence: 99%
“…The top 10 core genes which are most different between the two mice strain were Kng2, Kng1, Gnb3, Lpar3, Lpar1, Pik3r1, Pf4, Apob, Rps9, and Fbxo2. Recently Zhu et al found that Kng was negatively correlated with airway remodeling in human asthma, 34 Pik3r1 is an essential component of the PI3Kδ pathway, associated with immune system defects and dysregulation. 35 Athina et al demonstrated that reduced Apob in AR patients leads to decreased antioxidant capacity and impaired ability to inhibit monoclonal factor-κB expression and pro-inflammatory cytokine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, applications of proteomics to asthmatics after provocation using segmental allergen challenge or naturally induced exacerbations will be more robust for identifying activated pathways driving disease. Studies conducted since the publication of this review using paired segmental allergen challenge coupled with invasive BAL sampling show the presence of allergen-elicited fibrin cascade ( 6 ). An important observation from this work is that markedly diverse protein patterns are present during the exacerbation than what could be identified by analysis of stable disease.…”
mentioning
confidence: 99%